Valores energéticos da raspa integral de mandioca e do sorgo utilizados na alimentação de diferentes espécies e categorias de aves - Montenegro, Sebastian Dorado (2016)
Research that implements the use of alternative energetic ingredients for animal feed production has increased due to the high cost and, in some cases, low availability of corn. It is important to know the specific energy values for each specie and category of poultry in order to achieve the best production performance. In the literature, there are many studies conducted using broiler chickens which induce an inadequate extrapolation of energy values for other species. Therefore, the objective of this study was to determine the energy values of integral cassava root meal (ICRM) and ground sorghum for different species and categories of poultry. A metabolism assay was conducted with a randomized design, arranged in a factorial scheme 5 x 2, including five species/categories of birds and two test feeds, with six replications each. Experimental units (metabolic cage) were composed by: 5 Cobb 500 ® broiler chicks, with 21 days old; 3 Lomhann Brown pullets with 11 weeks of age; 3 Lomhann Brown laying hens, with 28 weeks of age; 10 growing Japanese quails (Coturnix japonica), with 4 weeks of age; and 10 laying Japanese quails with 30 weeks of age. Reference feeds were formulated for each specie/category of poultry and replaced by 30% and 40% ICRM and ground sorghum, respectively. The apparent metabolizable energy (AME), corrected apparent metabolizable energy for nitrogen balance (AMEn), the dry matter metabolizability coefficient (DMMC), and the crude energy metabolizability coefficient (CEMC) were determined. The results were submitted to variance analysis and when significant, compared by the Scott-Knott test at 5% of significance for each bird specie/category and by F test for ingredients, using SISVAR software version 5.6. There was interaction to the species/categories and feeds test for AME and AMEn, showing both of them the same relations. For ICRM, the highest values of AME and AMEn were found for pullets and laying quails. For sorghum, same energy values, for all the animals, were reported. There were also interactions for CEMC on which the lowest values for ground sorghum were found for pullets and highest values for ICRM were determined for pullets and laying quails. Interactions for DMMC revealed that lowest values were determined for ICRM when fed by broiler chicks and growing quail. Sorghum energetic values were the same between species/categories however is not recommended to extrapolate the ICRM energy values between bird species and categories.